Awareness, Coverage, and Barriers to COVID-19 Vaccination among Undergraduate Students in Nigeria - Fortune Benjamin Effiong; Ibrahim Adebayo Hassan; Dimeji Abdulsobur Olawuyi; Chiemela Prosper Ogbonna; Jeremiah Babatunde Araoye; Esther Edet Bassey; Kenneth Emeka Enwerem; Yusuff Adebayo Adebisi (University Library System, University of Pittsburgh, 2023)
Background: With the resumption of physical learning activities across Nigeria's higher education institutions, tertiary-level students, a priority group in the deployment of the COVID-19 vaccines according to the WHO SAGE, face circumstances that necessitate widespread vaccination coverage among them. This study aimed to assess Nigerian undergraduate students' knowledge, coverage, and barriers to COVID-19 vaccination. Method: A cross-sectional survey of Nigerian undergraduates was conducted in October 2021, using an online questionnaire and a combined simple random and snowballing sampling technique. The questionnaire included sections on respondents' demographic characteristics, COVID-19 vaccine awareness, coverage, barriers, and recommendations. A total of 326 respondents electronically completed and returned the informed consent form along with the questionnaire. The data obtained were analyzed using the statistical package for the social sciences (SPSS) version 25. Results: The overall awareness of COVID-19 vaccines among the sampled students was high; with 62.3%, 20.9%, and 16.9% having good, average, and poor levels of knowledge respectively. However, a majority of the respondents (81.3%) had not received the vaccines. The most prominent barrier to vaccination was misinformation about vaccine safety (23.6%). Opening vaccination centers on campuses (18.6%), demonstrating vaccine effectiveness and safety (18.7%), and organizing awareness campaigns (17.2%) were the most frequently recommended actions. Conclusion: Most respondents were aware of the availability and potential benefits of COVID-19 vaccines; however, coverage remained extremely low. Our findings emphasize the importance of addressing vaccination barriers by public health stakeholders to achieve optimal COVID-19 vaccine coverage.